2019
DOI: 10.1007/s10107-019-01367-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exact semidefinite formulations for a class of (random and non-random) nonconvex quadratic programs

Abstract: We study a class of quadratically constrained quadratic programs (QCQPs), called diagonal QCQPs, which contain no off-diagonal terms x j x k for j = k, and we provide a sufficient condition on the problem data guaranteeing that the basic Shor semidefinite relaxation is exact. Our condition complements and refines those already present in the literature and can be checked in polynomial time. We then extend our analysis from diagonal QCQPs to general QCQPs, i.e., ones with no particular structure. By reformulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 33 publications
2
76
0
Order By: Relevance
“…Recently, a number of exciting results in phase retrieval [17] and clustering [1,28,31] have shown that under various assumptions on the data, the QCQP formulation of the corresponding problem has a tight SDP relaxation. In contrast to these results, which address QCQPs arising from particular arXiv:2002.01566v1 [math.OC] 4 Feb 2020 problems, Burer and Ye [16] very recently gave appealing deterministic sufficient conditions under which the standard SDP relaxation of general QCQPs is tight. In our paper, we continue this vein of research for general QCQPs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of exciting results in phase retrieval [17] and clustering [1,28,31] have shown that under various assumptions on the data, the QCQP formulation of the corresponding problem has a tight SDP relaxation. In contrast to these results, which address QCQPs arising from particular arXiv:2002.01566v1 [math.OC] 4 Feb 2020 problems, Burer and Ye [16] very recently gave appealing deterministic sufficient conditions under which the standard SDP relaxation of general QCQPs is tight. In our paper, we continue this vein of research for general QCQPs.…”
Section: Introductionmentioning
confidence: 99%
“…
This note reports an error in Theorem 3 of [1], which was pointed about by Prof. Fatma Kılınç-Karzan and Mr. Alex Wang of Carnegie Mellon University, whom we sincerely thank for bringing this to our attention.The error can be seen in the proof of Theorem 3, where system ( 12) is analyzed for given diagonal matrices {C, B i , D i } and variable diagonal matrices {X , Y i }. In this setting, C, B i 0, while each D i is indefinite.
…”
mentioning
confidence: 87%
“…This note reports an error in Theorem 3 of [1], which was pointed about by Prof. Fatma Kılınç-Karzan and Mr. Alex Wang of Carnegie Mellon University, whom we sincerely thank for bringing this to our attention.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Rank-constrained optimization problems are considered in [28,29]. In [30], polynomial-time checkable sufficient conditions, which guarantees that the semidefinite relaxations of quadratically constrained quadratic programs are exact, are given.…”
Section: Introductionmentioning
confidence: 99%